Insight into schizophrenia: a comparative study between patients and family members - Gigante, Alexandre Duarte; Castel, Saulo (São Paulo Medical Journal, 2004)
CONTEXT: Despite the recognition of the role that sociocultural factors play in the process of acquiring insight, recent research on this issue is scarce. OBJECTIVES: 1) to translate and adapt the Schedule for Assessment of Insight (SAI) to Portuguese; 2) to use a modified version of it to evaluate family members’ insight into schizophrenia; 3) to compare patients’ insight with family members’ insight. TYPE OF STUDY: Cross-sectional study. SETTING: Schizophrenia Project Outpatient Clinic (Projesq), Institute of Psychiatry, Faculdade de Medicina da Universidade de São Paulo. METHODS: 40 patients with schizophrenia (Diagnostic and Statistical Manual for Mental Disorders – Fourth Edition — DSM-IV) undergoing outpatient treatment and members of their respective families were interviewed using the SAI and a modified version of this instrument, respectively. RESULTS: Family members performed better than patients in the total and partial SAI scores [total: 13.0 to 8.75 (p < 0.001); adherence: 3.9 to 3.4 (p < 0.005); recognition of illness: 5.5 to 3.5 (p < 0.001); relabeling of psychotic phenomena: 3.6 to 1.9 (p < 0.001)]. However, when the scores were correlated for each patient-family member pair, the only partial score that had a negative correlation was the relabeling of psychotic phenomena (r = -0.14), while the others had positive correlations (total r = 0.401; adherence r = 0.410; recognition of illness r = 0.422). DISCUSSION: There was a lack of correlation between the scores of family members and patients regarding the ability to relabel psychotic phenomena as abnormal. This might be understood as a smaller influence of sociocultural factors in this dimension than in other dimensions. The fact that family members were not assessed for the presence of psychopathology is a limitation of this study. CONCLUSIONS: Different dimensions of insight are not equally influenced by disease and sociocultural factors. The recognition of illness is more strongly influenced by sociocultural factors than the ability to relabel psychotic phenomena as abnormal.